Effect of Chronic Oxidative Stress on Neuroinflammatory Response Mediated by CD4+T Cells in Neurodegenerative Diseases - Solleiro-Villavicencio, Helena; Rivas-Arancibia, Selva (Frontiers in Cellular Neuroscience, 2018)
In a state of oxidative stress, there is an increase of reactive species, which induce an altered intracellular signaling, leading to dysregulation of the inflammatory response. The inability of the antioxidant defense systems to modulate the proinflammatory response is key to the onset and progression of neurodegenerative diseases. The aim of this work is to review the effect of the state of oxidative stress on the loss of regulation of the inflammatory response on the microglia and astrocytes, the induction of different CD4+T cell populations in neuroinflammation, as well as its role in some neurodegenerative diseases. For this purpose, an intentional search of original articles, short communications, and reviews, was carried out in the following databases: PubMed, Scopus, and Google Scholar. The articles reviewed included the period from 1997 to 2017. With the evidence obtained, we conclude that the loss of redox balance induces alterations in the differentiation and number of CD4+T cell subpopulations, leading to an increase in Th1 and Th17 response. This contributes to the development of neuroinflammation as well as loss of the regulation of the inflammatory response in neurodegenerative diseases such as Alzheimer’s (AD), Parkinson’s (PD), and Multiple Sclerosis (MS). In contrast, regulatory T cells (Tregs) and Th2 modulate the inflammatory response of effect of T cells, microglia, and astrocytes. In this respect, it has been found that the mobilization of T cells with anti-inflammatory characteristics toward damaged regions of the CNS can provide neuroprotection and become a therapeutic strategy to control inflammatory processes in neurodegeneration.